NiS2/MoS2 on carbon cloth as a bifunctional electrocatalyst for overall water splitting. (5th December 2019) - Wang, Xiangxi; Li, Lei; Wang, Zhao; Tan, Lin; Wu, Zhuoyan; Liu, Zhilinag; Gai, Shili; Yang, Piaoping
Abstract: Hydrogen plays a significant role in clean energy, such as in fuel cells, but the energy barrier severely restricts the efficiency of the hydrogen evolution reaction (HER). Electrocatalysts can eliminate the energy barrier to solve energy consumption and efficiency problems. Here, hierarchical NiS2 /MoS2 growing on carbon cloth (abbreviated as NiS2 /MoS2 -CC) is synthesized through a two-step process with bifunctional properties for both the HER and oxygen evolution reaction (OER). Different amounts of NiS2 are uniformly doped into MoS2 samples to optimize the composition. It is noted that the optimal NiS2 /MoS2 -CC electrode shows a good electrocatalytic performance and durability in a 1.0 M KOH alkaline solution for the HER, OER, and overall water splitting processes. This result demonstrates that the synergistic effect between MoS2 and NiS2 can enhance the electrocatalytic performance. Furthermore, NiS2 /MoS2 -CC as an electrode for overall water splitting shows good stability at low cell voltage. Our study demonstrates a potential method for overall water splitting. Graphical abstract: With low overpotential, NiS2 /MoS2 -CC can generate hydrogen and Oxygen in alkaline solution.Image 1